2018
DOI: 10.1021/acs.jpca.8b02311
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Aromatic and Photophysical Properties of Expanded Porphyrins

Abstract: Magnetically induced current densities and ring-current pathways have been calculated at density functional theory (DFT) and second-order Møller-Plesset perturbation theory (MP2) levels of theory for a set of expanded porphyrins consisting of five or six pyrrolic rings. The studied molecules are sapphyrin, cyclo[6]pyrrole, rubyrin, orangarin, rosarin, and amethyrin. Different functionals have been employed to assess the functional dependence of the ring-current strength susceptibility. Vertical singlet and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 84 publications
3
57
0
Order By: Relevance
“…Since it is known that some functional tends to overestimate the paratropic ring‐current strengths of strongly antiaromatic molecules, some authors recommend to employ also a functional with a larger percentage of HF exchange to avoid this kind of overestimation . Functional with about 50 % HF exchange yield ring current of about the same strength as obtained at the MP2 level . Therefore, for the most paratropic species C70 H10 and C100 H10 , we have repeated the calculation adopting the M06‐2X functional which has 54 % HF exchange, keeping same basis sets for geometry optimization and magnetic property calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Since it is known that some functional tends to overestimate the paratropic ring‐current strengths of strongly antiaromatic molecules, some authors recommend to employ also a functional with a larger percentage of HF exchange to avoid this kind of overestimation . Functional with about 50 % HF exchange yield ring current of about the same strength as obtained at the MP2 level . Therefore, for the most paratropic species C70 H10 and C100 H10 , we have repeated the calculation adopting the M06‐2X functional which has 54 % HF exchange, keeping same basis sets for geometry optimization and magnetic property calculation.…”
Section: Methodsmentioning
confidence: 99%
“…B3LYP calculations tend to overestimate the antiaromatic character of strongly antiaromatic molecules. It is therefore necessary to study the current densities using ab initio correlated levels of theory such as second-order Møller-Plesset perturbation theory (MP2) level or alternatively to employ a functional with a large fraction of Hartree-Fock exchange [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the strong antiaromaticity of porphyrinoids like carbaporphyrins, carbathiaporphyrins, isophlorins and expanded porphyrins has been shown to be due to a low-lying excited state that has a large magnetic dipole transition moment from the ground state [23][24][25]. The paratropic ring current of strongly antiaromatic porphyrinoids can result in closed-shell paramagnetic molecules [23].…”
Section: Introductionmentioning
confidence: 99%
“…We then calculated the magnetically induced current density using the GIMIC method, which is ar eliable means to determine the degree of aromaticity in aq uantitative manner. [24] Thep resent calculations revealed that the ring current of 2 is antiaromatic according to the magnetic criterion with an et current strength of À10.9 nA/T,w hereas the outer pyrrolic b-b carbon double bonds serve to produce al ocal diatropic current of about 2.0 nA/T (Figure 2a). The magnetically induced paratropic current preferably flows the inner pathway as highlighted with yellow lines in the streamline visualization (Figure 2b).…”
mentioning
confidence: 98%
“…[22,23] We report, herein, the first rational synthesis of 5,15dioxaporphyrin by an ucleophilic substitution reaction of anickel bis(dipyrrin) complex with benzaldoxime followed by an annulation reaction of the a-hydroxy-substituted intermediate.Inclear contrast to the nonaromaticity of its higher congener,5 ,15-dithiaporphyrin, [7,8] 5,15-dioxaporphyrin exhibited unequivocal antiaromatic characteristics,s uch as aparatropic ring current effect and abroad absorption in the visible and near-infrared (Vis/NIR) regions,r eflecting af orbidden HOMO-LUMO transition of an intrashell nature. Thecurrent-density calculations based on the gauge-including magnetically induced current (GIMIC) method [24] also provided quantitative information about the current pathway and the net paratropic ring current of À10.9 nA/T.…”
mentioning
confidence: 99%